A DINÂMICA DAS TERRITORIALIDADES NA COMUNIDADE DE FAXINAL DO POSTO INÁCIO MARTINS-PR - Lima, Lucélia Santos de (2011)
Inacio Martins PR compose the region known as the Paraná traditional retains many traditional features in their rural area, one of them is the presence of 12 faxinais communities, yet little studied. This research aims to understand, from empirical observation, the territorialities from Faxinal do Posto community, as reflected in religious events, economic and social. This required understanding the organization Faxinal system, adopting the concepts of territory and territoriality. We also seek to show from official surveys, the similarities and differences of faxinais from Inacio Martins. For to meet the objectives we have the following methodology: analysis of existing references from the subject faxinais, interviews with community residents faxinais from Inacio Martins, members of the public, representatives from EMATER, and through observation and perception of everyday community and questionnaires administered to students from Escola Estadual Aurea Lopes. By the hypothesis that the dynamics of territorial Faxinal do Posto is produced from day today community through their homes, plantations, fun but also through contact with external agents such that make them change their way of thinking and reproduce in its territory.